2014
DOI: 10.1371/journal.pone.0092844
|View full text |Cite
|
Sign up to set email alerts
|

In Others' Shoes: Do Individual Differences in Empathy and Theory of Mind Shape Social Preferences?

Abstract: Abundant evidence across the behavioral and social sciences suggests that there are substantial individual differences in pro-social behavior. However, little is known about the psychological mechanisms that underlie social preferences. This paper investigates whether empathy and Theory of Mind shape individual differences in pro-social behavior as conventionally observed in neutrally framed social science experiments. Our results show that individual differences in the capacity for empathy do not shape social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 65 publications
4
24
0
7
Order By: Relevance
“…Specifically, polite individuals behaved in accordance with fair distributions of wealth in the dictator game, whereas individuals with greater empathic concern were no more likely than others to allocate greater wealth to a partner after controlling for their good manners. The absence of a role for empathic concern fits with recent findings in which the capacity for empathy did not predict social preferences in neutrally framed dictator games (Artinger et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Specifically, polite individuals behaved in accordance with fair distributions of wealth in the dictator game, whereas individuals with greater empathic concern were no more likely than others to allocate greater wealth to a partner after controlling for their good manners. The absence of a role for empathic concern fits with recent findings in which the capacity for empathy did not predict social preferences in neutrally framed dictator games (Artinger et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, polite individuals behaved in accordance with fair distributions of wealth in the dictator game, whereas individuals with greater empathic concern were no more likely than others to allocate greater wealth to a partner after controlling for their good manners. The absence of a role for empathic concern fits with recent findings in which the capacity for empathy did not predict social preferences in neutrally framed dictator games (Artinger et al, 2014). Likewise, our results mirror the divergence of two correlates of real-world helping behaviors: dispositional empathic concern, the tendency to experience compassionate reactions to the needs of others, and the principle of care, the tendency to endorse a moral position of helping others (Wilhelm & Bekkers, 2010).…”
Section: Politeness and The Role Of Social Norms In The Dictator Gamesupporting
confidence: 90%
See 1 more Smart Citation
“…The Ultimatum Game (UG)7 has been one of the most prolific set-ups for unraveling the nature of human fairness over the last years13589101112131415161718. In this game, one player (the proposer) proposes a way to split a sum of money with another player (the responder).…”
mentioning
confidence: 99%
“…These studies showed that subjects' behaviour is not only a function of personal dispositions, but also depends on the context and the consequences of the other players' behaviour. More recently, Artinger, Exadaktylos, Koppel, and Sääksvuori (2014) investigated mind-reading in the wider framework of the Theory of Mind (ToM), stating that "utilizing ToM, the decision maker constructs the mental states of others making inferences about beliefs, intentions, and emotions".…”
Section: Please Scroll Down For Articlementioning
confidence: 99%